ANALISIS EFEKTIVITAS ASESMEN FORMATIF BERBENTUK PROYEK KELOMPOK PADA MATA PELAJARAN IPAS KELAS III MATERI EKOSISTEM - Mulyaningsih, Wulan; Ulia, Nuhyal (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The quality of learning is strongly influenced by the quality of assessment carried out by teachers in the teaching and learning process. In order to achieve the desired learning objectives, a teacher needs an evaluation tool. One form of evaluation that teachers can do is formative assessment activities. Formative assessment plays an important role in helping teachers identify the strengths and challenges faced by students in understanding the material. The effectiveness of formative assessment activities will be very influential. This study aims to analyze the effectiveness of formative assessment in the form of group projects in IPAS class III elementary school subjects. The research method used in this research is descriptive qualitative. To obtain the required data, researchers used data collection techniques through observation which then described the findings in the field and synthesized the findings by interpreting supporting reference sources. The data analyzed in depth and described in this study is the suitability of the assessment with the concept of development, environment, and abilities of students in class III SDN Banyumanik 03. The results of this article show that formative assessment through project activities in learning IPAS class III about biotic and abiotic ecosystems is proven to be in line with the needs and stages of cognitive development of students.